Spent equilibrium catalyst as internal curing agent in UHPFRC - Matos, Ana Mafalda (2019)
The main goal of the current paper is to optimize ultra-high performance cementitious material (UHPC) mixes incorporating the spent equilibrium catalyst (ECat) to mitigate autogenous shrinkage. Design of experiments approach was used to optimize mixtures targeting different engineering properties, namely, self-compactibility, low early-age shrinkage and cracking risk, improved durability and high mechanical performance. The statistical models established indicated that ECat exhibits a strong positive effect on the autogenous shrinkage mitigation of UHPC attributed to the water absorbed in the porous of ECat particles. The proposed optimal UHPC mixture represents the best compromise between low autogenous shrinkage ? 32% of reduction ? and high resistivity at 28 days without impairing self-compatibility and compressive strength. This optimal UHPC combined with 3% high-strength steel fibres (lf/df=65) proved to be comparable to other Ultra High-Performance Fibre Reinforced Composites (UHPFRC), in terms of mechanical behaviour, and more eco-friendly and cost-efficient than UHPCs reported in the literature.